Why Has Poverty Increased in Zimbabwe? - Alwang, Jeffrey; Mills, Bradford F.; Taruvinga, Nelson (Washington, DC: World Bank, 2013)
Poverty in Zimbabwe increased significantly during the 1990s, and it increased in all sectors of the economy. In the middle of the decade, more than 60 percent of Zimbabwean households fell below the national poverty line. There are competing reasons for this: some say it was the result of the government instituting the Economic Structural Adjustment Program (ESAP), and others say that ESAP's effectiveness was hampered by recurring drought. This document sheds light on the sources of the increase in Zimbabwean poverty, with the use of non-parametric, and parametric statistical methods. These techniques support the conclusion that the drought, though harmful, does not entirely explain the increase in poverty. The deteriorating economic environment, reducing the returns to both human, and physical assets, also had profound effects on household well-being. What are the prospects for improvement in the near future? Only serious structural changes to the economy can create labor market conditions, conducive to long-term, broad-based growth.